2022
DOI: 10.3389/fimmu.2022.908034
|View full text |Cite
|
Sign up to set email alerts
|

Alternative B Cell Differentiation During Infection and Inflammation

Abstract: Long-term protective immunity to infectious disease depends on cell-mediated and humoral immune responses. Induction of a strong humoral response relies on efficient B cell activation and differentiation to long-lived plasma cells and memory B cells. For many viral or bacterial infections, a single encounter is sufficient to induce such responses. In malaria, the induction of long-term immunity can take years of pathogen exposure to develop, if it occurs at all. This repeated pathogen exposure and suboptimal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…We observed a similar strong upregulation of T-bet in both naïve and memory B cells sorted from healthy blood donors, while the memory B cells were somewhat more efficient at upregulating CD11c and FcRL5 after 2 days of stimulation ( supplementary figure 3 ). As both naïve and memory B cells could efficiently respond to the stimuli, and in vivo generated CD11c-, T-bet − , and FcRL5-expressing cells are likely generated from both naïve and memory B cells [23], we used total B cells isolated from healthy blood donors to further characterise the response to stimulation ( Figure 2A ). Cell marker expression was evaluated by flow cytometry after stimulation with anti-Ig (BCR ligation), CpG-C (TLR9-ligation), and the pro-inflammatory cytokine IFN-γ in comparison to unstimulated cells ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed a similar strong upregulation of T-bet in both naïve and memory B cells sorted from healthy blood donors, while the memory B cells were somewhat more efficient at upregulating CD11c and FcRL5 after 2 days of stimulation ( supplementary figure 3 ). As both naïve and memory B cells could efficiently respond to the stimuli, and in vivo generated CD11c-, T-bet − , and FcRL5-expressing cells are likely generated from both naïve and memory B cells [23], we used total B cells isolated from healthy blood donors to further characterise the response to stimulation ( Figure 2A ). Cell marker expression was evaluated by flow cytometry after stimulation with anti-Ig (BCR ligation), CpG-C (TLR9-ligation), and the pro-inflammatory cytokine IFN-γ in comparison to unstimulated cells ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have described how the cell surface proteins CD11c and FcRL5 and the intracellular transcription factor T-bet are dynamically regulated after infection and following in vitro stimulation via different activation pathways. These proteins are commonly used in different combinations together with CD21, CD27, and IgD to identify a subset of B cells expanding during inflammatory conditions [23]. In a previous study of CD11c + B cells in malaria, we observed that these cells displayed different co-expression with FcRL5 and CXCR3 over time [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ activates cells via the JAK1/2 and STAT1 pathways and directly promotes secretion of CXCL9 and CXCL10, which are elevated during TB disease, via its effect on monocytes. CXCL9 and CXCL10 in turn promote the recruitment of activated NK cells, cytotoxic T cells, NKT cells, and B cells that have upregulated the homing receptor CXCR3 [54,55]. STAT1-driven immunity associated with IFN-γ (type II IFN) and TNF is important for Mtb control [56,57], whereas an early strong response associated with type I IFNs (IFN-α/β) has been associated with progression to TB disease [58].…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…They found these CD11c + ABC accumulated in unimmunized aged and young autoimmune‐prone mice (Manni et al, 2018 ; Rubtsov et al, 2011 , 2013 ) and that they played a key role in autoimmunity. The Marrack ABC resembled extrafollicular (EF) B cells, or atypical B cells, that develop in autoimmunity (Jenks et al, 2018 ; Rubtsova et al, 2017 ) and in chronic infections in humans (Courey‐Ghaouzi et al, 2022 ; Sutton et al, 2021 ) as all share CD11c and T‐bet expression. Thus, there is compelling evidence that ABC are a unique B cell population that develops with age and that ABC play key roles in autoimmunity and are associated with aged responses to chronic infection in both mice and humans.…”
Section: Introductionmentioning
confidence: 99%